Gold ETFs vs. Equity ETFs: Comparative Analysis of their Performance - Naveen, Kumara R. (International Journal of Social Sciences and Management, 2016)
Exchange-traded funds (henceforth, ETFs) are passive investment vehicles which have become increasingly popular in a relatively short period of time due the benefits they provide when compared to Mutual Funds and other similar investment avenues. This study has been carried out to analyze the points of distinction between the two very popular forms of ETFs namely Gold ETFs and Equity ETFs. These funds are similar in their functioning however it is necessary to understand the difference in their performance so as to be able to choose the right market instrument for investing our money. Our research project aims at understanding this difference because performance is one of the major factors affecting the popularity of any investment option. Int. J. Soc. Sc. Manage. Vol. 3, Issue-3: 222-227